Nevus lipomatosus cutaneous superficialis (Hoffman-Zurhelle) over lower back: a rare presentation - Mandadi, Santosh Reddy; Rao G., Venkateswara; Kilaru, Krishna Rajesh; Munnangi, Pooja (International Journal of Research in Dermatology, 2020)
Nevus lipomatosus cutaneous superficialis is a rare benign local malformation of the skin characterized by ectopic adipocytes in the dermis. It presents as either a classical type known as Hoffman-Zurhelle or the solitary type. We report a case of the classical type with multiple soft, non-tender, cerebriform, skin-colored papules and nodules over the lower back in a 16 years old female.